2013
DOI: 10.1213/ane.0b013e31828a739e
|View full text |Cite
|
Sign up to set email alerts
|

The VeinViewer Vascular Imaging System Worsens First-Attempt Cannulation Rate for Experienced Nurses in Infants and Children with Anticipated Difficult Intravenous Access

Abstract: The VeinViewer worsened first-attempt IV insertion success by skilled nurses. Surprisingly, first-attempt success for IV cannulation was not worsened by obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 18 publications
0
50
0
3
Order By: Relevance
“…Overall, trials of near infrared technologies in emergency department 7,8 and operating room settings [15][16][17] have not shown a convincing clinical benefit of nearinfrared imaging for peripheral intravenous catheteriza tion relative to the standard approach.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, trials of near infrared technologies in emergency department 7,8 and operating room settings [15][16][17] have not shown a convincing clinical benefit of nearinfrared imaging for peripheral intravenous catheteriza tion relative to the standard approach.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the efficacy of these devices is mixed . Researchers have found positive effects of VVT on first‐attempt success for venepuncture and catheter placement , number of venepuncture attempts per patient , time to conduct venepuncture or catheter placement , staff‐rated vein visibility , staff‐ and patient‐rated pain and average number of veins counted .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found positive effects of VVT on first‐attempt success for venepuncture and catheter placement , number of venepuncture attempts per patient , time to conduct venepuncture or catheter placement , staff‐rated vein visibility , staff‐ and patient‐rated pain and average number of veins counted . Some studies have shown null or even negative effects of VVT. Furthermore, studies in this domain have been criticized for inappropriate randomization, limited samples, poor standardization of procedures and a lack of consideration of device training or operator experience .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Peterson, Phillips, Truemper, and Agrawal (2012) found that unassisted methods proved to be more successful in PIV insertion success than the VeinViewer R assisted methods. VeinViewer R also decreased first attempt PIV insertion success among skilled nurses, 47% success versus 62% success by routine cannulation, in a study done by Szmuk, Steiner, Pop, Farrow-Gillespie, Mascha, and Sessler (2013). Vein visibility is enhanced, but near-infrared devices do not improve cannulation (De Graaff et al, 2013).…”
Section: Review Of Literaturementioning
confidence: 96%